Tracking the ancestry of known and 'ghost' homeologous subgenomes in model grass Brachypodium polyploids. (8th February 2022) - Sancho, Rubén; Inda, Luis A.; Díaz‐Pérez, Antonio; Des Marais, David L.; Gordon, Sean; Vogel, John P.; Lusinska, Joanna; Hasterok, Robert; Contreras‐Moreira, Bruno; Catalán, Pilar
Significance Statement: We designed a subgenome detection pipeline (PhyloSD) that allowed us to identify the three known and four ghost diploid progenitor genomes of six grass Brachypodium allopolyploids, and to infer the hypothetical evolutionary scenarios for their origins. Our pipeline can be used with either transcriptome or genome data, and retrieves the progenitor subgenomes of both allopolyploid and autopolyploid species. SUMMARY: Unraveling the evolution of plant polyploids is a challenge when their diploid progenitor species are extinct or unknown or when genome sequences of known progenitors are unavailable. Existing subgenome identification methods cannot adequately infer the homeologous genomes that are present in the allopolyploids if they do not take into account the potential existence of unknown progenitors. We addressed this challenge in the widely distributed dysploid grass genus Brachypodium, which is a model genus for temperate cereals and biofuel grasses. We used a transcriptome‐based phylogeny and newly designed subgenome detection algorithms coupled with a comparative chromosome barcoding analysis. Our phylogenomic subgenome detection pipeline was validated in Triticum allopolyploids, which have known progenitor genomes, and then used to infer the identities of three subgenomes derived from extant diploid species and four subgenomes derived from unknown diploid progenitors (ghost subgenomes) in six Brachypodium polyploids ( B. mexicanum, B. boissieri, B. retusum, B. phoenicoides, B. rupestre and B. hybridum ), of which five contain undescribed homeologous subgenomes. The existence of the seven Brachypodium progenitor genomes in the polyploids was confirmed by their karyotypic barcode profiles. Comparative phylogenomics of nuclear versus plastid trees allowed us to formulate hypothetical homoploid hybridizations and allo‐ and autopolyploidization scenarios that could have generated the six Brachypodium polyploids.